Neurodevelopment in infants with moderate neonatal risk and its association with biological and environmental factors - Vericat, Agustina (2019)
Moderate-risk neonates (MRNs) are newborns who usually remain hospitalized in neonatal intensive care units (NICU) after birth. Although they have low rates of mortality, morbidity burden may be significant and involve neurological risk. The aim of this study was to estimate the prevalence of neurodevelopmental disorders and the influence of biological and socio-environmental factors on the neurodevelopment of MRN. A cross-sectional study was performed on a sample of 162 MRNs aged 2–24 months, who remained in NICU ≥ 72 h after birth, with gestational age (GA) ≥ 34 weeks, birth weight ≥ 1500 g, and normal neurological and clinical examinations by the time of hospital discharge. Four neurodevelopmental areas were assessed using the Argentinian test PRUNAPE: language (LG), fine and gross motor skills (FM and GM), and personal-social skills (PS). Data from biological (gestational, perinatal and postnatal) and socio-environmental factors were collected through parental questionnaires. Thirty-four percent of infants failed the test. Gross motor was the most affected area (14.2%), followed by LG (11.7%), FM (7.4%), and PS (4.3%). Among gestational factors global failure was associated with drugs and alcohol consumption (p ≤ 0.029). Language was associated with maternal smoking (p = 0.007; OR 3.5), FM (p = 0.009; OR 13.0), and GM (p = 0.002; OR 10.6) with drug use, and both LG (p = 0.000; OR 22.6) and GM (p = 0.007; OR 16.2) with alcohol consumption during pregnancy. Infants born by cesarean had a higher risk of failure than those born by vaginal delivery (p = 0.049; OR: 2.2), as well as infants with pathological complementary diagnosis (p = 0.001; OR 2.7). Mechanical ventilation was associated with FM disorders (p = 0.025; OR 4.2). Children with siblings had a higher risk of failing the test than only children (p = 0.041; OR 2.0). Rate of neurodevelopmental disorders in MRN exceeds widely that of the general population. GM was the most affected area. Maternal addictions, cesarean birth, pathological complementary studies, MV, and having siblings are factors associated with failure in the screening.